Influence of seaweed extracts on growth, phytochemical contents and antioxidant capacity of cowpea (Vigna unguiculata L. Walp). (January 2019) - Vasantharaja, Raguraman; Abraham, L. Stanley; Inbakandan, D.; Thirugnanasambandam, R.; Senthilvelan, T.; Jabeen, S.K. Ayesha; Prakash, P.
Abstract: In this study, seaweed extracts were extracted from two seaweeds viz. Sargassum swartzii (brown seaweed) (SSE) and Kappaphycus alvarezii (red seaweed) (KAE). The seaweed extracts SSE and KAE were comparatively analyzed to assess the growth, yield, phytochemical content and antioxidant capacity of Vigna unguiculata . It was observed that the 3% SSE spray significantly improved the shoot length (33 cm), number of leaves (28), yield (40 g/pot), total phenolic content (36.64 µg GAE/g FW), protein (0.42 mg/g) and flavonoids (7.36 µg QCE/g FW) compared to the control. The DPPH (2, 2-diphenyl-1-picrylhydrazyl) radical scavenging activity was also high in 3% SSE spray. The major antioxidant compound was identified using methanolic extracts of Vigna unguiculata through GC-MS analysis. The results suggested that application of brown seaweed extract (SSE) with the concentration of 3% can significantly improve the phytochemical content and antioxidant activity in Vigna unguiculata thus enhancing its nutritional quality. Graphical abstract: fx1 Highlights: Sargassum swartzii extract (SSE) significantly enhanced plant growth and yield. SSE significantly improves the phenolic and flavonoid content in Vigna unguiculata . There were increases in the antioxidant activity following SSE treatments. The major antioxidant compound was identified in cowpea extract using GC-MS.